Energy signature of ton TNT-class impacts: analysis of the 2018 December 22 fireball over Western Pyrenees. Issue 4 (18th October 2021) - Anghel, S; Drolshagen, E; Ott, T; Birlan, M; Colas, F; Nedelcu, D A; Koschny, D; Zanda, B; Bouley, S; Jeanne, S; Malgoyre, A; Blanpain, C; et al.
ABSTRACT: The increase in detector sensitivity and availability in the past three decades has allowed us to derive knowledge of the meteoroid flux and impact energy into the Earth's atmosphere. We present the multi-instrument detected 2018 December 22 fireball over Western Pyrenees, and compare several techniques aiming to obtain a reliable method to be used when measuring impacts of similar scale. From trajectory data alone, we found a bulk density of 3.5 g cm −3 to be the most likely value for the Pyrenean meteoroid. This allowed to further constrain the dynamic mass, which translated into a kinetic energy of 1 ton TNT (4.184 × 10 9 J). For the second energy derivation, via the fireball's corrected optical radiation, we obtained a more accurate empirical relation measuring well-studied bolides. The result approximates to 1.1 ton TNT, which is notably close to the nominal dynamic result, and agrees with the lower margin of the seismic-based energy estimation, yet way lower than the infrasound estimate. Based on the relation derived in this study, we consider the nominal estimate from both the dynamic and photometric methods to be the most accurate value of deposited energy (1 ton TNT). We show that the combination of these two methods can be used to infer the meteoroid density. Among the methods presented in this paper, we found that the optical energy is the most reliable predictor of impact energy near the ton TNT-scale.